2014
DOI: 10.1002/nur.21621
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Feasibility of¡Cuídate!With Mexican and Central American Youth in a Rural Region of a Southern State

Abstract: Regions of the US with growing Latino populations are in need of culturally sensitive sexual risk reduction programs. A Latino community, a public school district, and a university in eastern North Carolina collaborated to test the feasibility of ¡Cuídate!, a culturally tailored, evidence-based sexual risk reduction program, with Mexican and Central American youth. Ten male and 10 female adolescents, ages 13-17 years, participated in the ¡Cuídate! program and post-program focus groups. Early adolescent boys an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Follow-up studies also found that the ¡Cuídate! intervention stimulated healthy communication about sex, condom use, and correct condom application for Mexican adolescent boys and girls (Larson, Ballard, Nuncio, & Swanson, 2014). These results support the notion that a culturally tailored intervention for Latina youth can be effective, especially for young adolescents (Douglas et al, 2014).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Follow-up studies also found that the ¡Cuídate! intervention stimulated healthy communication about sex, condom use, and correct condom application for Mexican adolescent boys and girls (Larson, Ballard, Nuncio, & Swanson, 2014). These results support the notion that a culturally tailored intervention for Latina youth can be effective, especially for young adolescents (Douglas et al, 2014).…”
supporting
confidence: 67%
“…Programs like ¡Cuídate! followed girls 6 and 12 months post-intervention and found continued success of their interventions (Larson, Ballard, Nuncio, & Swanson 2014; Villarruel et al, 2006). Future research with L-GEMM should continue follow-ups longer than 3 months to validate ongoing beneficial outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…The implementation plan should include a strategy for program monitoring and evaluation of implementation outcomes (i.e., high level of program fidelity or retention of program participants) as well as program outcomes (i.e., did participants gain knowledge and skill). Implementation outcome data can be used to test the feasibility of implementing a specific program with a new audience with whom the program has not been tested (e.g., Larson, Ballard, Nuncio, & Swanson, ) or to ensure consistency in program implementation regardless of setting or facilitator. Implementation outcomes may moderate or mediate program outcomes.…”
Section: Using the Fle Implementation Frameworkmentioning
confidence: 99%
“…Fidelity checklists typically include a list of all curriculum components and measure adherence to this curriculum. A participant observer can use the checklist to ensure that core components have been included in the program delivery, to record any adaptations made, or determine whether the curriculum has been implemented as intended (Larson et al, ). Other types of observation checklists or facilitator checklists can be used to capture levels of participant engagement and participant responsiveness, facilitator behaviors, or other aspects of design or delivery, such as information about specific teaching strategies.…”
Section: Using the Fle Implementation Frameworkmentioning
confidence: 99%